Biotechnological Induction of Shikimate-based Antioxidant Accumulation in Phyla dulcis - O. Osuji, Godson; Gao, Ming; Carson, Laura; Ampim, Peter; Weerasooriya, Aruna; Johnson, Paul; Duffus, Eustace; Woldesenbet, Sela; Kirven, Jeneanne; L. Williams, Ebonee; Johnson, Dewisha; Clarke, Diadrian (Natural Products Journal, The, 2017)
Background: Medicinal phytochemicals have been used as dietary supplements in Asia and Africa for thousands of years. Biologically active antioxidants are very diverse and low in their chemical compositions thereby limiting their efficacies. The present study focuses on the enhanced accumulation of closely related dietary antioxidants: shikimate, quinate, salicylate and tocopherol in Phyla dulcis, the Central American herb known for its anti-inflammatory medicinal properties; but its polyphenolic antioxidants had not been studied. Methods: Phyla dulcis stem cuttings were planted in the greenhouse, and in field plots and treated with solutions of stoichiometric mixes of mineral salts known to double crop biomass and yield. Controls were treated with water. At maturity, P. dulcis shoots and flowers were harvested per treatment, immediately frozen in liquid nitrogen, and submitted to metabolomic analyses by gas chromatography-time-of-flight mass spectrometry. Results: Field plot P. dulcis treated with KKS-mineral salts combination induced increased shikimate accumulation of 1.59 g per 100 g from the 0.799 g per 100 g in the untreated control. Similarly salicylate, quinate, and tocopherols increased in accumulation by many orders of magnitude in the stoichiometric mixes of mineral salts-treated P. dulcis compared with the untreated controls. Conclusion: The accumulated polyphenolic antioxidants permitted the deduction of the unique biosynthetic pathway of the shikimate, with a massive inhibition at the enzyme steps of dehydroquinate dehydratase and shikimate dehydrogenase.
Keywords: shikimate dehydrogenase